(untitled) (Scientific journal of the Fergana State University, 2023)
Biologically active substances are used in medicine and in the prevention of diseases, as well as to ensure a high level of vital activity. This article provides information on the biologically active substances found in peanuts, their beneficial properties and chemical structure.